PROINFLAMMATORY CYTOKINE PROFILE IN PATIENTS WITH DIFFERENT ALPHA-1-ANTITRYPSIN PHENOTYPES - M. Yu. Pervakova (SPb RAACI, 2016)
Alpha-1-antitrypsin (A1AT) exerts a wide spectrum of protective effects, being focused on reduction of secondary injury in inflammation. Moreover, A1AT inhibits some serine proteases, and down-regulates production of proinflammatory cytokines. A number of known A1AT phenotypes is accompanied by affection of cytokine profile in inflammatory processes, thus increasing the risk of disorders associated with A1AT deficiency.The aim of our study was to evaluate cytokine profiles in the patients with different A1AT phenotypes. Were collected eighty-six blood sera from the persons with suspected A1AT deficiency. The A1AT phenotypes and concentrations were determined in these samples. The patients were divided into four groups, depending on their A1AT variants, i.e., PiMM, PiZZ, PiMZ and rare A1AT phenotypes. The serum levels of IFNγ, TNFα, IL-6, IL-8, and IL-17 were measured in these groups by means of ELISA technique.The mean levels of IL-6 comprised 73.52±4.363 pg/ml in the patients with PiZZ phenotype, being higher than in cases of PiMM phenotype (45.61±8.01 pg/ml, p < 0.05). The IL-17 levels were also found to be increased in the groups with PiZZ and PiMZ phenotypes, as compared with PiMM phenotype (p < 0.001). The mean IL-17 values in the samples with PiZZ, PiMZ, and PiMM phenotypes were 80.13±13.56 pg/ml, 106.7±26.28 pg/ml and 42.73±18.52 pg/ml, respectively. Meanwhile, there were no significant differences in IL-8, IFNγ and TNFα levels among different A1AT phenotypes. The results of this study let us conclude that the cytokine imbalance may be crucial to onset of diseases associated with A1AT deficiency.